La polémica jurídica y política sobre la reforma a la ley de seguridad social en donde se elimina el aporte del 40 por ciento por parte del estado al Instituto Ecuatoriano de Seguridad Social - Guevara Buitrón, Mariuxi Carolina (2017)
The right to social security is a fundamental human right guaranteed not only by our Constitution, but also by treaties, conventions and declarations ratified by Ecuador, is an important right for members of society thus access the same guarantees that all citizens have a decent life, being the call of state to protect and ensure the effective enjoyment of that right. The enactment of the Ley Orgánica para la Justicia Laboral y Reconocimiento del Trabajo en el Hogar has triggered various legal problems, because, this legal standard contain amendments to several laws, the most controversial reform the Ley a la Seguridad Social to financing Instituto Ecuatoriano de Seguridad Social (IESS), in which it is determined that the subsidiary State to that institution only when it does not have sufficient funds to cover benefits which performs its affiliates, nor establishes the percentage must give the state for this item, mentioned directly affects older adults in the payment of retirement pensions therefore does not clearly establish the percentage and each time than the State must grant this subsidy IESS, is likely to that institution into economic deficit that end up affecting the payment of retirement pensions, in breach of the fundamental right to social security with older adults. In this research the rules of international law, the Constitution of Ecuador, and other laws that contain the right to social security as well as the principles of progressivity and regressivity of fundamental rights of the human being analyzed, with the in order to determine whether the IESS finance reform observes the constitutional and legal provisions guaranteeing the principle of progressive rights. The purpose of this is to establish the shortcomings of the IESS finance reform and their possible consequences against of retirees, and thus be a contribution in the search for solutions to this issue.